Studi Literatur: Pengaruh Perceraian Orang Tua Terhadap Motivasi Belajar Siswa - Rizki Rosalinda Siregar,; Isma Alif ,; Anggita Maritsha ,; Tiara Amelda, (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The increasing divorce rate in Indonesia is an important concern because it has a significant impact on children's well-being and motivation to learn. This study aims to analyze (1) the effect of parental divorce on students’ learning motivation, (2) the comprehensive factors leading to divorce, and (3) educational intervention strategies to mitigate its impact. The research employs a library research method with content analysis of national and international academic sources. The findings indicate that literature consistently report students’ motivation and academic achievement through psychosocial and economic mechanisms, such as decreased emotional support, financial instability, and family stress. Divorce factors are multifactorial, including prolonged conflicts, infidelity, domestic violence, and emotional immaturity. Effective interventions include strengthening parental involvement, school counseling services, social support, and government policies centered on child welfare. Therefore, schools and social institutions play a vital role in maintaining the academic and emotional development of students affected by parental divorce.